Rancangan Pelaksanaan Eksploitasi Nikel pada Blok X PT Paramitha Persada Tama Desa Boenaga Kecamatan Lasolo Kepulauan Kabupaten Konawe Utara Provinsi Sulawesi Tenggara - Hendri Pranata; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2021)
PT. Paramitha Persada Tama is a company engaged in mining, especially nickel mining. PT. Paramitha Persada Tama itself has an IUP area of 175 Ha. PT. Paramitha Persada Tama conducts nickel mining with an open-pit mining system (surface mining) with the Cut and Fill method. To meet the production target of 30,000 tons/month with a Cut Of Grade (COG) value of 1.4% Ni and market demand of 1.8% Ni. The purpose of this study is to determine the amount of reserves in block X that will be exploited and how to design the stages of nickel mining in the company. From the estimation results carried out using the Inverse Distance Weight (IDW) obtained 843,975 tons of Ni. Based on the results of the Pit design that has been designed get the pit limit or the end of mining at elevation 40 masl. And alsodesign pits that have been designed sharedover several stages (Sequence). The phasingdone is staging period long(long term). In the first stage, the total mined reserves are 227,370 ton and overburden unloaded was 902,085 bcm. In the second stage, the reserves amounted to 565,950 tons and the overburden unloaded was 732,415 bcm and in the third phase, the reserves amounted to 50.655 tons with an overburden volume of 110,000 bcm.Keyword : Mineplan, Pit Design, Reserve, IDW, Sequence